PELATIHAN BUDIDAYA HIDROPONIK SKALA RUMAHAN DAN PEMANFAATAN LIMBAH NON-ORGANIK DI DESA RAMANG, KECAMATAN BANAMA TINGANG, KABUPATEN PULANG PISAU: Muhamad Rangga1*, Haryati Sinaga2*, Yotam Meykisandi3*, Ermi Santika4*, Ayu Lestari Doloksaribu5*, Waidah6*, Dinnar Katon Wicaksono7*, Badarbendu Paningal8*, Dewi Lestari9*, Nurul Hidayah10*, Nina Sugiarti11*, Ferdinan Josi12*, Muhammad Habriyanoor Al aziz13*, Meylia Yuniarti14*, Apriliari Karisma Sensa15* - Muhamad Rangga1*, Haryati Sinaga2*, Yotam Meykisandi3*, Ermi Santika4*, Ayu Lestari Doloksaribu5*, W (Politeknik Seruyan, 2024)
A training on household-scale hydroponic cultivation was conducted in Ramang Village, Banama Tingang District, Pulang Pisau Regency, Central Kalimantan, on August 10, 2024. The activity aimed to introduce farming techniques without extensive land, increase knowledge about hydroponics, and build awareness of non-organic waste utilization. The methods used included socialization, discussion, and hands-on practice using the Wick System. Participants consisted of women, men, PKK team members, and housewives. The training results showed that hydroponics is a good alternative for farming in limited spaces and flood-prone areas. This technique allows the community to meet their daily food needs at an affordable cost using simple materials such as used plastic bottles. The activity successfully motivated the community to develop agriculture, improve food security, and promote a healthier lifestyle. This training is planned to be continued sustainably to maximize its benefits for the Ramang Village community.